ألإنهزام النفسي وعلاقته بالتسويف الأكاديمي وتحصيل ركض فعالية(400م حواجز) لدى طلاب الصف الثاني كلية التربية البدنية وعلوم الرياضة - جامعة صلاح الدين - كريم, فرهاد إبراهيم (Sulaimani Journal for Humanities, 2021)
The study aimed to identify self- defeatism and academic procrastination in second stage students of physical education /Salahaddin University, as well as to identify the relationship between them, moreover, to identify the relationship between self- defeatism and 400 m hurdles achievement in the sample of the study. The sample of the study consisted of (46) 2nd stage students of physical education /Salahaddin University in academic year (2020-2021). The researcher used correlational method in his study. Self- defeated scale was used which was developed by (Hazm Alwan and Farhad Ibrahim, 2017) which consists of 45 sections, also academic procrastination scale which developed by (Abu Ghazal, 2012) which consists of 21 sections. The results showed a significant relationship between Self- defeat and academic procrastination and significant difference in the relationship between Self- defeat and academic procrastination. Self- defeat: it is a state of collapse of students psychological resistance, inability feeling, helplessness, and lack of personal effectiveness, which faces physical educations fourth- stage students as a result of Frustration, despair and pessimist in terms of understanding the study materials from the cognitive and practical aspects which makes him/her devastated in terms of psychological, emotional, social, intellectual and economical aspects. The researcher reached a number of conclusions, including the distinction of the research sample members with a low level of self- defeat ism and a medium level of academic procrastination, and the research sample individuals were distinguished by an average level of achievement with a low effectiveness between self- defeatism and academic procrastination variables, offset by a medium or close to average effectiveness between self- defeatism academic, procrastination and achievement in the sample. And reached to a number of recommendations, including holding qualitative lectures and seminars to guide new students to help them adapt to the university and to know the reasons that drive students to procrastinate, and help them how to organize and manage time and provide more services and entertaining activities to keep them away from the causes of self- defeatism and procrastination, as well as conducting more research looking at reasons of defeatism.
Keywords: self defeat; academic procrastination; 400m hurdles achievement